Composite particles, positive electrode, all-solid-state battery, and method for producing composite particles
The composite particle design with a phosphorus-coated lithium nickel manganese oxide addresses cobalt scarcity and high resistance issues in sulfide-based all-solid-state batteries by optimizing Li composition in the coating film, resulting in reduced interfacial resistance and improved battery performance.
Patent Information
- Application Number
- JP2022062304
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-04-04
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2042-04-04
AI Technical Summary
Conventional lithium nickel-cobalt-manganese oxide positive electrode active materials face challenges due to the scarcity of cobalt and high resistance issues, particularly in sulfide-based all-solid-state batteries, where direct contact between the sulfide solid electrolyte and the positive electrode active material particles leads to increased resistance.
A composite particle design is introduced, comprising lithium nickel manganese oxide with a layered rock salt structure coated with a phosphorus compound, where the Li composition ratio in the coating film is optimized to reduce the interface resistance by minimizing Li diffusion and maintaining coating film flexibility, achieved through a controlled synthesis and heat treatment process.
The optimized composite particles significantly reduce interfacial resistance, enhancing the performance of all-solid-state batteries by maintaining ion conductivity and preventing the formation of lithium manganate phases that degrade battery characteristics.
Smart Images

Figure 0007655264000002 
Figure 0007655264000003 
Figure 0007655264000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite particle, a positive electrode, an all-solid-state battery, and a method for producing the composite particle. [Background technology]
[0002] Patent Document 1 (JP 2016-39062 A) discloses a positive electrode composite material and a sulfide all-solid-state battery having a positive electrode active material made of lithium nickel manganese oxide with a layered structure and a glass electrolyte that coats the surface of the positive electrode active material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-39062 A Summary of the Invention [Problem to be solved by the invention]
[0004] Conventionally, lithium nickel-cobalt-manganese oxide, a ternary material, has been widely used as a positive electrode active material. However, since cobalt (Co) is a rare metal, there is a demand for a positive electrode active material that does not contain Co.
[0005] Lithium nickel manganese oxide is an example of a material for a positive electrode active material that does not contain Co. Although lithium nickel manganese oxide is useful as a material for a positive electrode active material that does not contain Co, it is not easy to synthesize. In addition, it has the problem of low output characteristics (high resistance).
[0006] Therefore, it has been proposed to form a coating film on the surface of the positive electrode active material particles. For example, in a sulfide-based all-solid-state battery, the coating film is expected to reduce the resistance by preventing direct contact between the sulfide solid electrolyte and the positive electrode active material particles. However, there is room for improvement in reducing the resistance.
[0007] Therefore, an objective of the present disclosure is to reduce drag. [Means for solving the problem]
[0008] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0009] [1] The composite particles include positive electrode active material particles and a coating film. The positive electrode active material particles include lithium nickel manganese oxide having a layered rock salt structure. The lithium nickel manganese oxide having a layered rock salt structure is represented by the following formula (1).
[0010] Li a Ni x Mn 1-x O2(1) In the above formula (1), a satisfies the relationship of 0.95≦a≦1.10, and x satisfies the relationship of 0.48≦x≦0.52.
[0011] The coating film covers at least a part of the surface of the positive electrode active material particles. The coating film contains a phosphorus compound.
[0012] The composite particles satisfy the relationship of the following formula (2). C Li / C P <=2.5 (2) In the above formula (2), C Li indicates the elemental concentration of lithium (Li) determined from the peak area of the Li1s spectrum measured by X-ray photoelectron spectroscopy. P indicates the elemental concentration of phosphorus (P) determined from the peak area of the P2p spectrum measured by X-ray photoelectron spectroscopy.
[0013] In the synthesis of lithium nickel manganese oxide with a layered rock salt structure, it is known that increasing the ratio of Li to nickel manganese produces lithium manganese oxide with an excess of Li in the transition metal layer of the layered rock salt structure. Because the Li diffusion rate of lithium manganese oxide is slow, even if it is produced locally, it can cause a decrease in battery performance.
[0014] In addition, as disclosed in Patent Document 1, after forming a coating film containing a phosphorus compound (Li3PO4) on the surface of the positive electrode active material particles, a heat treatment may be performed to stabilize the coating film. However, the heat treatment causes Li in the coating film to diffuse into the positive electrode active material, resulting in the local generation of lithium manganate, which degrades the battery characteristics.
[0015] In addition, the Li composition ratio on the surface of the composite particle is considered to reflect the Li composition ratio in the coating film. In a conventional coating film, for example, Li3PO4, the Li composition ratio is considered to be 3.0 or more. In Li3PO4, Li ions are considered to be carriers. Therefore, the more carriers there are, the more improved ion conductivity is expected. In other words, the greater the Li composition ratio in the phosphorus compound, the more reduced the battery resistance is expected.
[0016] However, according to the new findings of the present disclosure, by reducing the composition ratio of Li in the phosphorus compound, it is possible to reduce the probability of voids occurring at the interface between the positive electrode active material and the solid electrolyte when the coating film is densified while maintaining the flexibility of the coating film, and it is expected that the resistance will be reduced. In addition, even after the above-mentioned heat treatment, it is possible to suppress the Li in the coating film from diffusing into the positive electrode active material and forming a different phase such as lithium manganate near the surface of the positive electrode active material, and it is expected that the resistance will be reduced.
[0017] [2] The composite particles may have a coverage of, for example, 80% or more. The coverage is measured by X-ray Photoelectron Spectroscopy (XPS).
[0018] [3] The positive electrode includes the composite particles according to [1] or [2] above and a sulfide solid electrolyte.
[0019] [4] The all-solid-state battery includes the positive electrode described in [3] above. [5] A method for producing composite particles includes the following (a) and (b):
[0020] (a) A mixture is prepared by mixing a coating liquid with positive electrode active material particles. (b) drying the mixture to produce composite particles.
[0021] The coating liquid contains a phosphoric acid compound and a solvent. The coating liquid adhered to the surface of the positive electrode active material particles is dried to form a coating film. The coating liquid described in [5] above can form the coating film described in [1] above.
[0022] [6] The solute may include, for example, a phosphate compound. The coating liquid may satisfy, for example, the relationship of the following formula (3).
[0023] 0≦n Li / n P <1.1 (3) In the above formula (3), n Li indicates the molar concentration of lithium in the coating solution. P indicates the molar concentration of phosphorus in the coating solution.
[0024] [7] (b) above may include forming composite particles, for example by spray drying. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing the all-solid-state battery in this embodiment. [Diagram 3] FIG. 3 is a schematic flow chart of the method for producing composite particles in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure.
[0027] <Definitions of terms, etc.> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0028] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0029] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only a single particle, but also an aggregate of particles (powder, powder, particle group).
[0030] Unless otherwise specified, the order of execution of steps, operations, and the like included in various methods is not limited to the order described. For example, multiple steps may proceed simultaneously. For example, multiple steps may be performed in sequence.
[0031] For example, a numerical range such as "m to n%" includes the upper limit and the lower limit unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0032] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may be allowed.
[0033] "D50" refers to the particle size at which the cumulative frequency from the small particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method. For example, a laser diffraction type particle size distribution measuring device "Product name SALD-7500" (or an equivalent product) manufactured by Shimadzu Corporation may be used.
[0034] <XPS Measurement> (composition ratio of particle surface) C in the above formula (2) Li , C Pcan be measured by the following procedure. An XPS instrument is prepared. For example, an XPS instrument manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is set in the XPS instrument. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, an analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used. The peak area (integral value) of the Li1s spectrum is used to determine the elemental concentration of Li (C Li ) The peak area of the P2p spectrum is converted to the elemental concentration of P (C P ) is converted to C Li C P By dividing by Li / C P ) is obtained.
[0035] (Coverage rate) The coverage is also measured by XPS. By analyzing the above measurement data, the ratio of each element can be obtained from the peak areas of C1s, O1s, P2p, Ni2p3, and Mn2p3.
[0036] The coverage rate is calculated by the following formula (4). θ=P / (P+Ni+Mn)×100 (4) In the above formula (4), θ represents the coverage (%), and P, nickel (Ni), and manganese (Mn) represent the ratios of each element.
[0037] <Film thickness measurement> The film thickness (thickness of the coating film) can be measured by the following procedure. A sample is prepared by embedding composite particles in a resin material. A cross-section is processed on the sample by an ion milling device. For example, an ion milling device "Product name Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by an SEM (Scanning Electron Microscope). For example, an SEM device "Product name SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The film thickness is measured in five fields of view for each of 10 composite particles. The arithmetic average of the film thicknesses at a total of 50 points is regarded as the film thickness.
[0038] 《ICP measurement》 (Composition ratio of positive electrode active material particles) The a and x in the above formula (1) can be measured by the following procedure. A standard solution is prepared by diluting 0.01 g of positive electrode active material particles with pure water. An inductively coupled plasma atomic emission spectroscopy (ICP-AES) device is prepared. For example, an ICP-AES device manufactured by Shimadzu Corporation, product name ICPE-9000 (or an equivalent product) may be used. The emission intensity of the standard solution is measured by the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The mole fractions of Li, Ni, and Mn contained in the positive electrode active material particles are determined from the emission intensity of the sample solution and the calibration curve.
[0039] (P adhesion amount) The mass fraction of P contained in the composite particles (also referred to as "P attachment amount" or "P content") can be measured by the following procedure. A mixed acid is prepared by mixing hydrochloric acid, nitric acid, and sulfuric acid. The mixing ratio is "hydrochloric acid / nitric acid / sulfuric acid = 2 / 3 / 1 (molar ratio)". A solution is prepared by dissolving the composite particles in the mixed acid. A sample solution is prepared by diluting 0.01 g of the solution to 100 mL with pure water. An aqueous solution of P (1000 ppm, 10000 ppm) is prepared. A standard solution is prepared by diluting 0.01 g of the aqueous solution with pure water. An ICP-AES device is prepared. For example, an ICP-AES device "Product name ICPE-9800" (or an equivalent product) manufactured by Shimadzu Corporation may be used. The emission intensity of the standard solution is measured by the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The mass fraction of P contained in the composite particles is determined from the emission intensity of the sample solution and the calibration curve.
[0040] (Mass concentration of Li, P, and Na in the coating solution) The mass concentrations of Li, P, and Na in the coating liquid are measured in the following procedure. 100 ml of sample liquid is prepared by diluting 0.01 g of the coating liquid with pure water. Aqueous solutions of Li, P, and Na (1000 ppm, 10000 ppm) are prepared. A standard solution is prepared by diluting 0.01 g of the aqueous solution with pure water. An ICP-AES device is prepared. The emission intensity of the standard solution is measured using the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The emission intensity of the sample liquid (diluted solution of the coating liquid) is measured using the ICP-AES device. The mass concentrations of Li, P, and Na in the coating liquid are determined from the emission intensity of the sample liquid and the calibration curve. The mass concentrations of Li and P are then converted to molar concentrations. The molar concentration of Li (n Li ) is the molar concentration of P (n P ) to obtain the molar ratio (n Li / n P ) is obtained.
[0041] <Composite particles> FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. The composite particle 5 may be called, for example, a "coated positive electrode active material". The composite particle 5 includes a positive electrode active material particle 1 and a coating film 2. The composite particle 5 may form, for example, an aggregate. That is, one composite particle 5 may include two or more positive electrode active material particles 1. The composite particle 5 may have, for example, a D50 of 1 to 50 μm, a D50 of 1 to 20 μm, or a D50 of 5 to 15 μm.
[0042] The coating film 2 is a shell of the composite particle 5. The coating film 2 covers at least a part of the surface of the positive electrode active material particle 1. The coating film 2 contains a phosphorus compound. By including the phosphorus compound in the coating film 2, a reduction in resistance is expected.
[0043] The phosphorus compound may contain, for example, Li, oxygen (O), carbon (C), etc. P may be contained in the composite particle 5 at a mass fraction of, for example, 0.2 to 10%.
[0044] In the composite particle 5, the composition ratio of the particle surface (C Li / C P The composition ratio (C) is 2.5 or less (see formula (2) above). Li / C P By making the composition ratio (C) 2.5 or less, the resistance can be significantly reduced. Li / C P The composition ratio (C) may be, for example, 2.4 or less, 2.2 or less, or 1.73 or less. Li / C P ) may be zero. Li / C P ) may be, for example, 0.1 or more, 0.5 or more, or 1.0 or more. Li / C P ) may be, for example, 1.73 to 2.5.
[0045] The coverage may be, for example, 80% or more. A coverage of 80% or more is expected to reduce resistance. The coverage may be, for example, 85% or more, 86% or more, 89% or more, or 91% or more. The coverage may be, for example, 100%, 99% or less, or 95% or less. The coverage may be, for example, 85 to 91%.
[0046] The coating film 2 may have a thickness of, for example, 5 to 100 nm, 5 to 50 nm, 10 to 30 nm, or 20 to 30 nm.
[0047] The positive electrode active material particle 1 is a core of the composite particle 5. The positive electrode active material particle 1 may be a secondary particle (aggregation of primary particles). The positive electrode active material particle 1 (secondary particle) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm.
[0048] The positive electrode active material particles 1 may contain any component. The positive electrode active material particles 1 contain a lithium-containing composite oxide having a layered rock salt structure. The crystal structure of the positive electrode active material particles 1 can be identified by, for example, X-ray diffraction (XRD) or the like. The lithium-containing composite oxide is represented by the following formula (1).
[0049] Li a Ni x Mn 1-x O2(1) In the above formula (1), a satisfies the relationship of 0.95≦a≦1.10, and x satisfies the relationship of 0.48≦x≦0.52. When a exceeds 1.10, lithium manganate is generated in the transition metal layer of the layered rock salt structure, which may decrease the Li diffusion rate and increase the resistance. When a is less than 0.95, Li is insufficient in the positive electrode active material particles 1, which may decrease the crystallinity during synthesis and increase the resistance. When x exceeds 0.52, the battery characteristics (cycle characteristics) may decrease. When x is less than 0.48, lithium manganate is generated in the transition metal layer of the layered rock salt structure, which may decrease the Li diffusion rate and increase the resistance. It is preferable that a satisfies the relationship of 1.00≦a≦1.10. The lithium-containing composite oxide may be, for example, Li 0.95 Ni 0.5 Mn 0.5 O2, Li 1.05 Ni 0.5 Mn 0.5 It may be O2 or the like.
[0050] <All-solid-state battery> 2 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 100 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of an aluminum laminate film. The exterior body may house a power generating element 50. The power generating element 50 includes a positive electrode 10, a separator layer 30, and a negative electrode 20. That is, the all-solid-state battery 100 includes a positive electrode 10, a separator layer 30, and a negative electrode 20.
[0051] 《Positive electrode》 The positive electrode 10 is layered. The positive electrode 10 may include, for example, a positive electrode active material layer and a positive electrode current collector. For example, the positive electrode active material layer may be formed by applying a positive electrode mixture to the surface of the positive electrode current collector. The positive electrode current collector may include, for example, aluminum (Al) foil or the like. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0052] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the separator layer 30. The positive electrode active material layer includes a positive electrode mixture. The positive electrode mixture includes composite particles and a sulfide solid electrolyte. That is, the positive electrode 10 includes composite particles and a sulfide solid electrolyte. Details of the composite particles are as described above.
[0053] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, with respect to 100 parts by volume of the composite particles (positive electrode active material). The sulfide solid electrolyte includes, for example, Li, P, and sulfur (S). The sulfide solid electrolyte may further include, for example, O, silicon (Si), or the like. The sulfide solid electrolyte may further include, for example, a halogen, or the like. The sulfide solid electrolyte may further include, for example, iodine (I), bromine (Br), or the like. The sulfide solid electrolyte may be, for example, glass ceramics or argyrodite. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.
[0054] The positive electrode active material layer may further include, for example, a conductive material. The conductive material may form an electronic conduction path in the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake.
[0055] The positive electrode active material layer may further include, for example, a binder. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).
[0056] 《Negative electrode》 The negative electrode 20 is a counter electrode of the positive electrode 10. The negative electrode 20 is layered. The negative electrode 20 may include, for example, a negative electrode active material layer and a negative electrode current collector. For example, the negative electrode active material layer may be formed by applying a negative electrode mixture to the surface of the negative electrode current collector. The negative electrode current collector may include, for example, a copper (Cu) foil, a Ni foil, or the like. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0057] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the separator layer 30. The negative electrode active material layer includes a negative electrode mixture. The negative electrode mixture includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode mixture may further include a conductive material and a binder. The sulfide solid electrolyte may be the same or different between the negative electrode mixture and the positive electrode mixture. The negative electrode active material particles may include any component. The negative electrode active material particles may include, for example, graphite, Si, silicon oxide [SiO x (0 <x<2)〕、およびLi4Ti5O 12 may contain at least one selected from the group consisting of:
[0058] <Separator layer> The separator layer 30 is interposed between the positive electrode 10 and the negative electrode 20. The separator layer 30 separates the positive electrode 10 from the negative electrode 20. The separator layer 30 includes a sulfide solid electrolyte. The separator layer 30 may further include a binder. The sulfide solid electrolyte may be the same or different between the separator layer 30 and the positive electrode composite. The sulfide solid electrolyte may be the same or different between the separator layer 30 and the negative electrode composite.
[0059] <Method of manufacturing composite particles> 3 is a schematic flow chart of the method for producing composite particles in this embodiment. Hereinafter, the "method for producing composite particles in this embodiment" may be abbreviated as "this production method". This production method includes "(a) preparation of a mixture" and "(b) production of composite particles". This production method may further include, for example, "(c) heat treatment" or the like.
[0060] (a) Preparation of the mixture The present manufacturing method includes preparing a mixture by mixing a coating liquid with positive electrode active material particles. The details of the positive electrode active material particles are as described above. The mixture may be, for example, a suspension or a wet powder. For example, a suspension may be formed by dispersing positive electrode active material particles (powder) in a coating liquid. For example, a wet powder may be formed by spraying a coating liquid into a powder. In the present manufacturing method, any mixing device, granulating device, etc. may be used.
[0061] The coating liquid contains a solute and a solvent. The solute contains a film material (raw material of the coating film). The coating liquid may further contain, for example, a suspended solid (insoluble component), a precipitate, and the like.
[0062] The amount of the solute may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass, relative to 100 parts by mass of the solvent. The solvent may contain any component as long as the solute dissolves therein. The solvent may contain, for example, water, alcohol, etc. The solvent may contain, for example, ion-exchanged water, etc.
[0063] The solute may include, for example, a phosphoric acid compound. This allows the solute to contain P. The phosphoric acid compound may be, for example, phosphoric anhydride (P2O5), orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid [(HPO3) n ] and polyphosphoric acid. The phosphate compound may be, for example, at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid. Metaphosphoric acid and polyphosphoric acid may have a longer molecular chain than other phosphate compounds. It is considered that the phosphate compound has a long molecular chain, which makes it easier to generate a coating film having continuity. The coating film having continuity is expected to, for example, improve the coverage rate.
[0064] The solute may further contain sodium (Na). When Na is dissolved in the coating liquid, the stability of the phosphate compound may be improved. The concentration (mass concentration) of Na in the coating liquid may be, for example, 0 to 1%. The concentration of Na may be, for example, 0.6% or less, or 0.5% or less. The concentration of Na may be, for example, 0.5 to 0.6%.
[0065] The solute may further include a lithium compound. The solute may include, for example, lithium hydroxide, lithium carbonate, lithium nitrate, etc. The molar ratio of Li to P (n Li / n P ) may be, for example, less than 1.1 (see formula (3) above). Li / n P ) is less than 1.1, so that the composition ratio (C Li / C P ) is expected to decrease. Li / n P ) may be, for example, 1.07 or less, 0.45 or less, or zero. Li / n P) may be, for example, 0 to 0.45 or 0.45 to 1.07.
[0066] (b) Production of Composite Particles The present manufacturing method includes producing composite particles by drying the mixture. The coating liquid attached to the surface of the positive electrode active material particles is dried to produce a coating film. In the present manufacturing method, any drying method can be used.
[0067] For example, the composite particles may be formed by a spray-drying method. That is, the suspension is sprayed from a nozzle to form droplets. The droplets contain the positive electrode active material particles and the coating liquid. For example, the droplets are dried by hot air to form the composite particles. The use of the spray-drying method is expected to improve, for example, the coverage rate.
[0068] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.
[0069] For example, the composite particles may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) preparation of the mixture" and "(b) production of the composite particles" can be carried out simultaneously.
[0070] (c) Heat Treatment The present manufacturing method may include subjecting the composite particles to a heat treatment. The coating film may be fixed by the heat treatment. The heat treatment may also be called "baking". In the present manufacturing method, any heat treatment device may be used. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air or in an inert atmosphere. EXAMPLES
[0071] The present embodiment will be described below using examples, but the present embodiment is not limited to these.
[0072] <Production of Positive Electrode Active Material Particles> Positive electrode active material particles A to D, which are lithium-containing composite oxides having a layered rock salt structure, were produced as follows.
[0073] 《Cathode active material particles A》 Nickel(II) sulfate hexahydrate (NiSO4·6H2O) and manganese(II) sulfate pentahydrate (MnSO4·5H2O) were dissolved in pure water to obtain a raw solution. The molar ratio of Ni and Mn in the raw solution was 1:1, and the total molar concentration of Ni and Mn in the raw solution was 1.8 mol / L.
[0074] 1 L of 10 g / L ammonia aqueous solution was prepared in a reaction vessel. 1 L of raw material aqueous solution was dropped into the reaction vessel at a rate of 5.2 mL / min, while adjusting the pH to within 11.20±0.2 using sodium hydroxide aqueous solution to form a precipitate, thereby obtaining a precursor. From the start to the end of the precipitation reaction, the ammonia aqueous solution was appropriately added so that the ammonia concentration of the reaction solution was 10 g / L.
[0075] The precursor was baked at 600°C for 12 hours in an air atmosphere, and then lithium carbonate (Li2CO3) was mixed in such that the molar ratio of Li to Ni and Mn was 1.05, and baked at 1000°C for 12 hours in an air atmosphere. The temperature was then gradually decreased to 850°C for 10 hours, 700°C for 10 hours, and 150°C for 20 hours, and cooled to obtain positive electrode active material particles A. The composition of positive electrode active material particles A was measured by the above-mentioned procedure. The results are shown in Table 1 below.
[0076] 《Cathode active material particles B~D》 Positive electrode active material particles B to D were obtained in the same manner as positive electrode active material particles A, except that lithium carbonate was mixed so that the molar ratios of Li to Ni and Mn were 0.95, 1.22, and 0.91, respectively. The compositions of positive electrode active material particles B to D were measured by the above-mentioned procedure. The results are shown in Table 1 below.
[0077] <Manufacturing of all-solid-state batteries> Composite particles, positive electrodes, and all-solid-state batteries according to Nos. 1 to 9 were produced as follows. Hereinafter, for example, "composite particles according to No. 1" may be abbreviated as "No. 1."
[0078] No.1 (Coating liquid) A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium hydroxide monohydrate (LiOH HO) was dissolved in the coating solution so that the refractive index was 0.75.
[0079] (positive electrode) Positive electrode active material particles A were prepared. 50 parts by mass of the positive electrode active material particles powder were dispersed in 53.7 parts by mass of the coating liquid to prepare a suspension. A spray dryer manufactured by BUCHI (product name: Mini Spray Dryer B-290) was prepared. The suspension was supplied to the spray dryer to produce a powder of composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. By the above procedure, the composition ratio (C Li / C P The composition ratio (C) and coverage of the particle surface were measured. The results are shown in Table 1. Li / C P ) and coverage were measured.
[0080] The following materials were prepared: Sulfide solid electrolyte: Li2S-P2S5-based glass ceramics containing LiI (D50: 0.8 μm) Conductive material: VGCF Binder: SBR Dispersion medium: heptane Positive electrode current collector: Aluminum foil The composite particles, the sulfide solid electrolyte, the conductive material, the binder, and the dispersion medium were mixed to prepare a positive electrode slurry. The mixture ratio of the composite particles and the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of the conductive material was 3 parts by mass for 100 parts by mass of the composite particles. The amount of the binder was 0.7 parts by mass for 100 parts by mass of the composite particles. The positive electrode slurry was thoroughly stirred using an ultrasonic homogenizer (Model UH-50) manufactured by SMT Corporation. The positive electrode slurry was applied to the surface of the positive electrode current collector to form a coating film. The coating film was dried at 100 °C for 30 minutes using a hot plate. In this way, a positive electrode blank was manufactured. A disk-shaped positive electrode was cut out from the positive electrode blank. The area of the positive electrode was 1 cm2. 2 It was.
[0081] (Negative electrode) The same materials as those for the positive electrode were prepared as the sulfide solid electrolyte, conductive material, binder, and dispersion medium. A Primix Corporation mixer (product name: Filmix, model: 30-L) was prepared as the mixer. The sulfide solid electrolyte, conductive material, binder, and dispersion medium were placed in the mixing vessel of the mixer. The materials in the mixing vessel were mixed at a rotation speed of 20,000 rpm for 30 minutes.
[0082] Li4Ti5O as negative electrode active material particles 12(D50: 1.0 μm), and Cu foil was prepared as a negative electrode current collector. Negative electrode active material particles were added to the stirring vessel. Stirring was performed at 15000 rpm for 60 minutes. The mixture ratio of the negative electrode active material particles and the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 7 / 3 (volume ratio)". The amount of the conductive material was 1 part by mass for 100 parts by mass of the composite particles. The amount of the binder was 2 parts by mass for 100 parts by mass of the composite particles. After the negative electrode active material particles were added, the materials in the stirring vessel were stirred at a rotation speed of 15000 rpm for 60 minutes to prepare a negative electrode slurry. The negative electrode slurry was applied to the surface of the negative electrode current collector to form a coating film. The coating film was dried at 100 ° C. for 30 minutes by a hot plate. In this way, a negative electrode raw material was manufactured. A disk-shaped negative electrode was cut out from the negative electrode raw material. The area of the negative electrode is 1 cm 2 It was.
[0083] (Separator layer) A Li2S-P2S5-based glass ceramic containing LiI (D50: 2.5 μm) was prepared as a sulfide solid electrolyte. 2 A cylindrical ceramic of 64.8 mg was placed in a mold, smoothed, and then subjected to a pressure of 1 ton / cm. 2 The separator layer was obtained by pressing and compacting the mixture at a pressure of 1000 MPa.
[0084] (All-solid-state battery) In the mold, a positive electrode was placed on one side of the separator layer, and a negative electrode was placed on the other side. 2 The negative electrode, separator layer, and positive electrode were pressed together for one minute with a pressure of 1 ton / cm. A stainless steel rod was placed between the positive and negative electrodes, and a pressure of 1 ton / cm was applied. 2 A power generating element was formed by binding the battery element with a binder. A pouch made of aluminum laminate film was prepared as a housing. The battery element was sealed in the housing. This resulted in the formation of an all-solid-state battery.
[0085] No.2 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium hydroxide monohydrate was dissolved in the coating solution so that the ratio of the ionic liquid to the total surface area was 0.45. After this, the composite particles, the positive electrode, and the all-solid-state battery were fabricated in the same manner as in No. 1.
[0086] No.3 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. No lithium hydroxide monohydrate was added to the coating solution. From this point on, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1.
[0087] No.4 Positive electrode active material particles B were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium hydroxide monohydrate was dissolved in the coating solution so that the σ was 0.60. After this, composite particles, a positive electrode, and an all-solid-state battery were fabricated in the same manner as in No. 1.
[0088] No.5 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate (LiNO3) was dissolved in the coating solution so that the σ was 3.00. From this point on, composite particles, positive electrodes, and solid-state batteries were produced in the same manner as in No. 1.
[0089] No.6 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate was dissolved in the coating solution so that the σ was 2.00. After this, composite particles, a positive electrode, and an all-solid-state battery were produced in the same manner as in No. 1.
[0090] No.7 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate was dissolved in the coating solution so that the σ was 0.80. After this, composite particles, a positive electrode, and an all-solid-state battery were produced in the same manner as in No. 1.
[0091] No.8 Positive electrode active material particles C were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate was dissolved in the coating solution so that the ratio of the ionic liquid to the total surface area was 0.70. After this, the composite particles, the positive electrode, and the all-solid-state battery were produced in the same manner as in No. 1.
[0092] No.9 Positive electrode active material particles D were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate was dissolved in the coating solution so that the ratio of the ionic liquid to the total surface area was 0.65. After this, the composite particles, the positive electrode, and the all-solid-state battery were produced in the same manner as in No. 1.
[0093] <Evaluation> The capacity of the evaluation battery was confirmed by constant current-constant voltage charging and constant current discharging. The charge / discharge time rate was 1 / 3C. "C" is the symbol for the time rate. At a time rate of 1C, the battery's full charge capacity is discharged in 1 hour.
[0094] The SOC (state of charge) of the evaluation battery was adjusted to 50% by a time rate of 1 / 3C. After adjusting the SOC, AC impedance measurements were performed. The amplitude was 10 mV. The frequency range was 0.1 to 10 6 Hz. A Cole-Cole plot was created from this. A circular arc was fitted to the Cole-Cole plot. The distance between the two intersections of the fitted circular arc with the real axis was determined. This distance was considered to be the "interface resistance." The interface resistance of each solid-state battery was evaluated relative to the interface resistance of the all-solid-state battery No. 1 as the reference (1.0). The results are shown in Table 1 below.
[0095] [Table 1]
[0096] <Result> The molar ratio a of Li in the positive electrode active material particles satisfies the relationship of 0.95≦a≦1.10, and the composition ratio (C Li / C P In Nos. 1 to 4, where the interfacial resistance is 2.5 or less, the interfacial resistance is significantly reduced.
[0097] Composition ratio of particle surface (C Li / C P In Nos. 5 to 7, in which the Li molar ratio a in the positive electrode active material particles was outside the range of 0.95≦a≦1.10, the coverage did not decrease but the interface resistance increased.
[0098] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]
[0099] 1 positive electrode active material particle, 2 coating film, 5 composite particle, 10 positive electrode, 20 negative electrode, 30 separator layer, 50 power generating element, 100 all-solid-state battery.
Claims
1. The positive electrode active material particles and the coating film are included, the positive electrode active material particles contain a lithium-containing composite oxide having a layered rock salt structure, The lithium-containing composite oxide having a layered rock salt structure has the following formula (1): Li a Ni x Mn 1-x O 2 (1) In the above formula (1), a satisfies the relationship 0.95≦a≦1.10, x satisfies the relationship 0.48≦x≦0.52, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film contains a phosphorus compound, The phosphorus compound is metaphosphoric acid, The following formula (2): C Li / C P ≦2.5 (2) Fulfilling the relationship, In the above formula (2), C Li indicates the elemental concentration of lithium determined from the peak area of the Li1s spectrum measured by X-ray photoelectron spectroscopy, C P indicates the elemental phosphorus concentration determined from the peak area of the P2p spectrum measured by X-ray photoelectron spectroscopy.
2. A coverage rate of 80% or more; The composite particle according to claim 1 , wherein the coverage is measured by X-ray photoelectron spectroscopy.
3. A positive electrode comprising the composite particle according to claim 1 or 2 and a sulfide solid electrolyte.
4. An all-solid-state battery comprising the positive electrode according to claim 3.
5. A method for producing the composite particle according to claim 1, comprising the steps of: (a) preparing a mixture by mixing a coating liquid with the positive electrode active material particles; and (b) drying the mixture to produce composite particles; Including, The coating liquid comprises a solute and a solvent.
6. The solute comprises a phosphate compound; The coating liquid has the following formula (3): 0≦n Li / n P <1.1 (3) Fulfilling the relationship, In the above formula (3), n Li represents the molar concentration of lithium in the coating solution, n P The method for producing composite particles according to claim 5 , wherein m represents a molar concentration of phosphorus in the coating liquid.
7. The method for producing composite particles according to claim 5 or 6, wherein the step (b) includes forming the composite particles by a spray drying method.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery and method for producing the same, and positive electrode for lithium secondary battery using the positive electrode active material and lithium secondary battery
JP2012038680A
Positive electrode composite material and sulfide all-solid battery arranged by use thereof
JP2016039062A
Positive electrode active material composite for lithium ion secondary battery and method for producing the same
JP2021048037A
Method for producing composite active material
JP2021099918A
Positive electrode active material for lithium secondary batteries, positive electrode for lithium secondary batteries, lithium secondary battery, method for producing positive electrode active material for lithium secondary batteries, and method for manufacturing lithium secondary battery
WO2017094416A1